Circular Economy: A Green Strategy to Achieve Farmer Independence and Food Self-Sufficiency - Yamin, Muhammad; Hafidzah, Nur Hidayatul; Hidayat, Taufiq (Civil and Military Cooperation Journal, 2025)
This study explores the role of the circular economy as a green strategy to empower farmers and achieve food self-sufficiency in Indonesia. Using a systematic literature review approach, the research synthesizes findings from national and international studies published between 2015 and 2024. The results reveal that circular practices—such as recycling crop residues and livestock manure into organic fertilizers, integrating crops with livestock and aquaculture, and processing surplus produce into value-added products—significantly enhance resource efficiency, reduce food loss, and diversify farmer income. These practices not only reduce reliance on imported agricultural inputs but also restore soil fertility, mitigate environmental impacts, and strengthen farmers’ bargaining power within food systems. At the macro level, embedding circular economy principles in agricultural policy aligns with the Sustainable Development Goals, particularly those related to zero hunger and responsible consumption, thus positioning Indonesia to move closer to food sovereignty. However, the study also identifies barriers including limited access to technology, financing, and knowledge, as well as fragmented policy support. Overcoming these challenges requires coordinated interventions in policy reforms, infrastructure investment, institutional strengthening, and digital innovation. Overall, the circular economy provides a transformative framework that enhances farmer independence while supporting sustainable food self-sufficiency.